Os ambientalismos chineses e suas paisagens - Danilo Caporalli Barbosa (2023)
China’s rise as a global economic power has upended the chessboard of global geopolitics. Amid Chinese economic advances and North American missteps, environmental policies have become a sensitive point between the two powers. Understanding the context that is being formed, this thesis maps the characteristics of Chinese environmentalism and its landscapes. To this end, this work proposes an opening to forms of environmentalism and landscapes not yet discerned, nourished by history, geography, philosophy, and art. In order to research these other environmental constructions, we made some choices: we chose to make short reports of places, projects, and stories, interspersed with theory; we also chose to hand-illustrate all the maps that are structured in a single language associated with architectural practice. Likewise, the chapters are organized by the commonality of symbolic elements of traditional Chinese landscape painting: water and mountains. The option for short reports was made after direct contact with Chinese culture on a 100-day trip. From this immersion, the classificatory nature of the research was replaced by a narrative practice. In the end, we identify the construction of Chinese ecocivilization as a project to change social formation that relies on the tangle of environmental relations to constitute itself in a planned, historical, institutionalized, and multiple way.